Autodesk architectural desktop 2006 - Onstiott, Scott (Sybex, 2005)
Autodesk Architectural Desktop (ADT) is the popular drafting and building-information-management (BIM) program that expands AutoCAD's feature set to include automatic documentation, "smart" objects, project-based palettes, and much more. All new from the world's best-selling AutoCAD publisher, this book is the ultimate resource for beginning through advanced ADT users. In the tradition of Sybex's illustrious Mastering series, you'll get the most comprehensive coverage in a mix of tutorials and detailed reference. The companion DVD includes the Autodesk Architectural Desktop demo as well as sample files and useful utilities. This book also features a foreword by Chris Yanchar, product planning manager.